Hubungan Diabetes Melitus Dan Merokok Dengan Kejadian Benign Prostatic Hyperplasia (BPH): Tinjauan Pustaka - Haikal Nirfandi; Khairun Nisa Berawi; Exsa Hadibrata (Medula, 2023)
Benign Prostatic Hyperplasia (BPH) is an enlargement of the prostate gland in the form of a histological disorder due to the proliferation of prostate cells. According to the World Health Organization (WHO), there are 70 million degenerative cases, and BPH is included in that, while in Indonesia there are 9.2 million cases of BPH, with the most occurring in men over 60 years old. There are several risk factors that can increase the likelihood of BPH, such as age, race, family history of BPH, hypertension, obesity, and sexual activity. Men who have had a vasectomy are also at high risk of developing BPH. In addition, a history of diabetes mellitus and smoking habits are also risk factors that can increase the likelihood of BPH. The content of nicotine and conitin in cigarettes can increase the activity of androgen-damaging enzymes, resulting in a decrease in testosterone levels.